Answer:
-5
Explanation:
Sometimes f(x) can be a little confusing. You never quite know where which number goes where.
Start with the first part
f(6) means that wherever you see an x on the right you put a 6.
So do this.
f(6) = (3/2)(6) +b =
equals what
(3/2) * 6 + b = 7 That's because f(6) = 7 Now just solve it
(18)/2 + b = 7
9 + b = 7
9 - 9 + b = 7 - 9
b = - 2
================
The entire equation is
y = (3/2)x - 2
===============
What happens when you are given
f(-2)
The - 2 means that wherever you see an x, let it be - 2
f(-2) = (3/2)(-2) - 2
f(-2) = -3 - 2
f(-2) = - 5
===============
You could think of f(x) being y. You will not go wrong doing that. y = f(x)